Towards the optimisation of direct laser acceleration. (18th February 2021) - Hussein, A E; Arefiev, A V; Batson, T; Chen, H; Craxton, R S; Davies, A S; Froula, D H; Gong, Z; Haberberger, D; Ma, Y; Nilson, P M; Theobald, W; et al.
Abstract: Experimental measurements using the OMEGA EP laser facility demonstrated direct laser acceleration (DLA) of electron beams to (505 ± 75) MeV with (140 ± 30) nC of charge from a low-density plasma target using a 400 J, picosecond duration pulse. Similar trends of electron energy with target density are also observed in self-consistent two-dimensional particle-in-cell simulations. The intensity of the laser pulse is sufficiently large that the electrons are rapidly expelled along the laser pulse propagation axis to form a channel. The dominant acceleration mechanism is confirmed to be DLA and the effect of quasi-static channel fields on energetic electron dynamics is examined. A strong channel magnetic field, self-generated by the accelerated electrons, is found to play a comparable role to the transverse electric channel field in defining the boundary of electron motion.